Spaceborne to UAV Bistatic Radar System for High-resolution Imaging and Autonomous Navigation - Rodriguez-Cassola, Marc; Younis, Marwan; Krieger, Gerhard; Oswald, Michael; Del Monte, Luca (European Conference on Synthetic Aperture Radar (EUSAR), 2010)
Bistatic radars offer several advantages when compared to their monostatic counterparts. In addition to increased performance, sensitivity, coverage and revisit times, all of them parameters which are mainly dependent on their spatial configuration, bistatic radars offer the objective advantage of being more robust to jamming, since the receiver operates as a mere passive system. The proposed system consists of a spacebore radar transmitter illuminating an area of interest and one or several radar receivers mounted on a UAV to perform a two-goal mission: a) help autonomous navigation of the UAV by performing the sense and avoid function, and b) perform surveillance of the overflown area using high-resolution remote sensing techniques. Although the requirements for these significantly different tasks might seem distant, having a spacebore transmitter ensures that the coverage needed for both puroses is achievable. The system can provide a cheap and robust manner for enabling global UAV flight, while enabling continuous all-weather imaging capabilities.
DLR Import::2019-04-03